Repurposed drugs as histone deacetylase 8 inhibitors: Implications in cancer and neuropathological conditions - Alrouji, Mohammed; Venkatesan, Kumar; Alshammari, Mohammed S.; Alhumaydhi, Fahad A.; Shafi, Sheeba; Sharaf, Sharaf E.; Shahwan, Moyad; Shamsi, Anas (Frontiers in Pharmacology, 2024)
Histone deacetylase 8 (HDAC8) is a member of class I histone deacetylases (HDACs) that catalyzes the deacetylation of both histone and non-histone proteins. Dysregulation and overexpression of HDAC8 are implicated in the development of various complex diseases, including cancer and neurodegenerative disorders. HDAC8 plays a significant role in cancer progression, contributing to cancer cell proliferation, metastasis, immune evasion, and drug resistance. The available HDAC8-targeting inhibitors suffer from poor target engagement, and low tolerability, and demonstrate off-target toxicity due to limited selectivity, leading to adverse effects in patients, and thus urging for the identification and development of new molecules. Drug repurposing is a useful strategy for identifying useful drugs for predefined targets which can be exploited here for identifying promising drug molecules against HDAC8. This study involved an integrated virtual screening against HDAC8 using the DrugBank database to identify repurposed drugs capable of inhibiting HDAC8 activity. The process started by selecting the top 10 drug molecules based on their binding affinity. The drug profiling and biological function of selected molecules were then evaluated showing anticancer and anti-neurological properties with a high probability of being active. Interaction analysis revealed crucial binding residue by Radotinib and Sertindole molecules with HDAC8 protein. Both molecules showed higher binding affinity than the reference inhibitor Droxinostat. The elucidated molecules were further taken for 500 ns longrun molecular dynamics (MD) simulation with HDAC8. Structural deviation, compactness, folding behavior, hydrogen bonds analysis, and secondary structure content profiling revealed complex stability formed by HDAC8 and the selected compounds. Principal component analysis and Gibbs free energy calculations strongly recommend that both complexes were highly stable during the simulation. Overall, the results indicate that Radotinib and Sertindole can be promising candidates as HDAC8 targeting repurposed drugs against cancer and neuropathological conditions.